Earlier Alzheimer's disease onset is associated with a shift of tau pathology towards brain hubs which facilitates tau spreading. (20th December 2022) - Franzmeier, Nicolai; Ewers, Michael; Brendel, Matthias; Biel, Davina; Ossenkoppele, Rik; Hager, Paul; Steward, Anna; Dewenter, Anna; Rubinski, Anna; Buerger, Katharina; Janowitz, Daniel; Binette, Alexa Pichet; et al.
Abstract: Background: In Alzheimer's disease (AD), younger symptom onset is associated accelerated cognitive decline and tau spreading, yet the drivers of faster disease manifestation in patients with earlier symptom onset are unknown. Earlier symptom onset is associated with stronger tau pathology in fronto‐parietal regions which typically harbor globally connected hubs that are central for cognition. Since tau spreads across connected regions, globally connected hubs may accelerate tau spreading due to their large number of connections to other brain regions. Thus, we hypothesized that a pattern shift of tau pathology towards globally connected brain hubs may facilitate tau spreading and earlier symptom manifestation in AD. Method: We included two independent samples with longitudinal Flortaucipir tau‐PET covering the AD spectrum (ADNI: n(controls/AD‐preclinical/AD‐symptomatic)=93/60/89, BioFINDER, n(controls/AD‐preclinical/AD‐symptomatic)=16/16/25). In addition, we included resting‐state fMRI from human connectome project participants (n=1000), applying a 200‐ROI brain atlas to obtain a global connectivity map for assessing brain hubs (Fig.1A‐D). Applying the same atlas to tau‐PET we transformed SUVRs to tau positivities using a pre‐established gaussian‐mixture modeling approach (Fig.1E‐F). By mapping tau‐PET positivities to the fMRI‐derived global connectivity map (Fig.1G‐L), we assessed the degree to which subject specific tau‐PET patterns were shifted towards globally connected hubs or non‐hubs, while adjusting for global tau levels. Using linear regression, we then tested whether a stronger shift of tau towards hubs was associated with earlier symptom manifestation and faster longitudinal tau accumulation. Result: In symptomatic AD patients, younger age was associated with a stronger shift of tau‐PET towards globally connected brain hubs (p[ADNI/BiOFINDER]=0.024/0.018, Fig.2A&B), and with higher global connectivity of epicenters with highest tau pathology (p[ADNI/BiOFINDER]<0.001/0.001, Fig.2C&D). In symptomatic AD, younger age (p[ADNI/BiOFINDER]=0.009/0.001) and a stronger shift of tau‐PET towards hubs predicted faster subsequent tau accumulation (p[ADNI/BiOFINDER]=0.004/0.002), supporting the view that that hubs facilitate tau spreading (Fig.3). Further, a stronger shift of tau‐PET towards globally connected brain hubs mediated the association between younger age and faster tau accumulation in symptomatic AD patients (p[ADNI/BiOFINDER]=0.039/0.046). Conclusion: Younger AD symptom onset is associated with stronger tau pathology in globally connected brain hubs, which facilitates faster tau spreading.